2024
DOI: 10.17645/pag.7441
|View full text |Cite
|
Sign up to set email alerts
|

Territorial Configurations of School‐To‐Work Outcomes in Europe

Ruggero Cefalo,
Rosario Scandurra,
Yuri Kazepov

Abstract: <p>Comparative research on school-to-work transitions mainly focused on country differences, examining the variation in institutional design and its impact on shaping youth labour market outcomes. The field has been dominated by a sort of methodological nationalism assuming nation states as homogeneous objects of comparison, while the territorial variations in youth transitions among sub-national territories have been less explored, notwithstanding their potential impact on life chances. In this article,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Specifically, comparative research has shown that contextual factors within EU regions may influence territorial configurations of school-to-work transitions, potentially exacerbating the challenges faced by low-skilled young people in disadvantaged contexts [8], highlighting significant regional inequality across European countries [9]. Indeed, in certain countries, young people completing their education face difficulties in overcoming barriers to entering the labour market, primarily stemming from their need to acquire the skills and additional competencies demanded by the labour market, often without adequate support [10].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, comparative research has shown that contextual factors within EU regions may influence territorial configurations of school-to-work transitions, potentially exacerbating the challenges faced by low-skilled young people in disadvantaged contexts [8], highlighting significant regional inequality across European countries [9]. Indeed, in certain countries, young people completing their education face difficulties in overcoming barriers to entering the labour market, primarily stemming from their need to acquire the skills and additional competencies demanded by the labour market, often without adequate support [10].…”
Section: Introductionmentioning
confidence: 99%